Mercado de trabalho jurídico no Brasil: Qual é a situaç\~ao atual? - André Gambier Campos; Roberto Di Benedetto (Instituto de Pesquisa Econômica Aplicada (IPEA), 2021)
– The purpose of this article is to describe, in a stylized way, the current situation of the legal labour market in Brazil. In other words, the situation of the market integrated by professionals: i) with complete higher education in law and, ii) occupied in jobs demanding this specific type of education (positions that will be called "legal occupations"). Despite the relevant dimension of the current legal market in Brazil, involving almost one million active professionals, there is a relative scarcity of academic studies, with an essentially empirical nature, able to describe this kind of labour market. This article seeks to mitigate such shortage by providing some new and updated figures from official databases.
Keywords: J00; J44; J49; 330; legal labour market; higher education in law